1984
DOI: 10.2113/gsecongeo.79.7.1540
|View full text |Cite
|
Sign up to set email alerts
|

Volcanogenic sulfide deposits in the southernmost Appalachians

Abstract: Volcanogenic massive sulfide deposits in the southernmost Appalachians of east-central Alabama and west-central Georgia are associated with metamorphosed submarine basalts and felsic rocks of the Ashland, Wedowee, and Talladega lithotectonic terranes. These three terranes lie between the Brevard fault on the south and the Talladega-Cartersville and Hayesville faults on the north. The oldest sulfide deposits occur in a regional setting characterized by a thick sequence of metamorphosed Eocambrian to lower Paleo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The amphibolite which encloses the deposits has been interpreted as a metamorphosed tholeiitic basalt (Whittington, 1982;Stow et al, 1984;Schafer and Coolen, 1986) and the enclosing pelitic metasedimentary rocks have been interpreted as metamorphosed fiysch-type sediments (Neathery and Hollister, 1984 rocks and the oxide facies iron-formations have been interpreted as altered basalts and exhalites, respectively (Whittington, 1982;Schafer and Coolen, 1986). On the basis of the above-lithological associations, their stratigraphic conformability, and the presence of hydrothermally altered rocks and exhalites, the FeZn-Cu deposits in the Stone Hill district have been interpreted by previous investigators as proximal volcanic-associated massive sulfide deposits (cf.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The amphibolite which encloses the deposits has been interpreted as a metamorphosed tholeiitic basalt (Whittington, 1982;Stow et al, 1984;Schafer and Coolen, 1986) and the enclosing pelitic metasedimentary rocks have been interpreted as metamorphosed fiysch-type sediments (Neathery and Hollister, 1984 rocks and the oxide facies iron-formations have been interpreted as altered basalts and exhalites, respectively (Whittington, 1982;Schafer and Coolen, 1986). On the basis of the above-lithological associations, their stratigraphic conformability, and the presence of hydrothermally altered rocks and exhalites, the FeZn-Cu deposits in the Stone Hill district have been interpreted by previous investigators as proximal volcanic-associated massive sulfide deposits (cf.…”
Section: Introductionmentioning
confidence: 99%
“…Whittington (1982) and Stow et al (1985) interpreted the felsic schists as metasedimentary rocks and concluded that the Stone Hill deposits formed along a spreading margin. Neathery and Hollister (1984) also interpreted the felsic schists as metasedimentary rocks but concluded that all of the deposits in the northern Piedmont formed in a backarc basin. Although Schafer and Coolen (1986) mentioned the possibility that the felsic schists may have formed by alteration, they interpreted them as rhyolitic metavolcanic-pyroclastic rocks.…”
Section: Introductionmentioning
confidence: 99%